Validating Questionnaires for Lower Limb Rehabilitation Systems and Devices: A Scoping Review - Angie D. Moscoso; Vera Z. Pérez; Manuel J. Betancur (Sports)
This article aims to make a scoping review of Validating Questionnaires used in the field of lower limb (LL) rehabilitation in which systems, devices or exergames are used. Its main objective is to provide a more comprehensive understanding of the results obtained in the validation of questionnaires, as well as to identify specific criteria for evaluating systems, devices or exergames in the area of LL rehabilitation, through the analysis of validating instruments and their application in different associated contexts. The article details the methodology employed, a PRISMA ScR method review which included database research and an evaluation of the selected studies. Inclusion and exclusion criteria were applied to select all relevant studies, resulting in 81 studies after initial review based on titles and abstracts. Subsequently, the criteria were again applied to read the full text, resulting in 58 final studies. The document distinguishes between standardized and non-standardized validating questionnaires, emphasizing that standardized validating questionnaires have undergone rigorous statistical processes to ensure their validity, reliability and consistency. The information compiled in the tables provides a solid basis for identifying and evaluating validation questionnaires in the above-mentioned context. This resource constitutes an accurate and reliable reference for selecting the most appropriate instruments for future research and comparisons with similar work. This article is a valuable resource for those interested in the validation of questionnaires used in the field of lower limb rehabilitation systems/devices/exergames.